PENGARUH MOTIVASI, KOMUNIKASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. TUJUH SUMBER BERKAH PANDEGLANG - Sri Ndaru Arthawati (LPPM Universitas Banten jaya, 2021)
ABSTRAK This study aims to determine the motivation (X1) Communication (X2) and work discipline (Y) on the performance of employees of PT. The Seven Blessings of Pandeglang, The method used in this research is quantitative research with a descriptive approach. The population of this research are all employees who work at PT. Seven Sources of Blessing Pandeglang precisely in the Department of Production and The sample of this study amounted to 40 employees of the Production Department of PT. seven sources of blessing pandeglang using saturated sampling technique, the data analysis technique used in this research is data quality test, including validity and reliability test, descriptive statistics, classical assumption test including normality test, multicollinearity test, heteroscedasticity test, autocorrelation test. And multiple linear regression analysis, T and F test and the coefficient of determination. The results of this study indicate the T Hypothesis Test that (1) Motivation has a positive and significant effect on employee performance (2) Communication has a positive and significant effect on employee performance (3) Work discipline has a positive and significant effect on employee performance. Keywords: Motivation, Communication, Work Discipline, Employee Performance